Charting the Diffusion of Power Sector Reforms across the Developing World - Foster, Vivien; Witte, Samantha; Banerjee, Sudeshna Ghosh; Moreno, Alejandro (World Bank, Washington, DC, 2017)
Some 25 years have elapsed since international financial institutions espoused a package of power sector reform measures that became known as the Washington Consensus. This package encompassed the establishment of autonomous regulatory entities, the vertical and horizontal unbundling of integrated national monopoly utilities, private sector participation in generation and distribution, and eventually the introduction of competition into power generation and even retail services. Exploiting a unique new data set on the timing and scope of power sector reforms adopted by 88 countries across the developing world over 25 years, this paper seeks to improve understanding of the uptake, diffusion, packaging, and sequencing of power sector reforms, and the extent to which they were affected by the economic and political characteristics of the countries concerned. The analysis focuses on describing the patterns of reform without judging their desirability or evaluating their impact. The paper finds that following rapid diffusion during 1995-2005, the spread of power sector reforms slowed significantly in 2005-15. Only a small minority of developing countries fully implemented the reform model as originally conceived. For the majority, reforms were only selectively adopted according to ease of implementation, often stagnated at an intermediate stage, and were sometimes packaged and sequenced in ways unrelated to the original logic. Country characteristics such as geography, income group, power system size, and political economy all had a significant influence on the uptake of reform. Moreover, a significant number of countries experienced reversals of private sector participation, or were unable to follow through with reform plans that were officially announced. Overall, power sector reform in the developing world lags far behind what was achieved in the developed world during the same time period. Yet, even in the developed world, the full package of reforms does not seem to have been universally adopted.